THE NORMAL AND THE PATHOLOGICAL: AN ANALYSIS OF PAUL RICOEUR'S AND GEORGES CANGUILHEM'S VIEWS (Isagoge - Journal of Humanities and Social Sciences, 2022)
The work presented here is an attempt to discuss the idea of ​​the normal and the pathological from the perspective of Canguilhem and Ricoeur. For this, an integrative review was carried out through the search for texts that contemplated the works on the normal and the pathological. And from there, through a re-reading of the main ideas of the authors, to understand their conceptions going through the internal directions of their arguments, and highlighting their relevance and relevance to contemporary debates in the life sciences in the course of the works cited.
Keywords: Normal and pathological; Paul Ricoeur; Georges Canguilhem; The just